Model Pendidikan Lingkungan Hidup Bagi Generasi Melenial Pada Era 4.0 (Kasus Pengelolan Hutan Di Desa Adat Tenganan) - Ni Wayan Karmini (Jayapangus Press, 2019)
This scientific work discusses the discussion of the implementation of local wisdom of the Tenganan Village indigenous people in managing forests and their meaning in environmental education for millennials in the 4.0 era. As a form of qualitative study, research data were obtained through observation, literature study, and in-depth interviews with 11 informants, namely observers of Balinese cultural tourism and customary interpreters of Tenganan Pegringsingan Village. The collected data were analyzed descriptively-qualitatively. The assessment results show that customary law forms awig-awig applied to the management of Tenganan Pengingsingan village tourism forest. The local Balinese community strongly agrees and implements these awig-awig, among others considered as part of the local nature, does not damage the potential of forest flora and fauna, and utilize forest products in an adaptive manner. The application of local wisdom (awig-awig) in managing the Tenganan forest is compatible with the direct application of growing protection that supports environmental preservation. The attitude and problems of the Tenganan community in forest management are adjusted to the model of direct education for local children in efforts to preserve the environment.